Дослідження архітектурних рішень користувацького інтерфейсу для ефективного використання мобільних додатків - Зеленська, Ю. Д. (ХНУРЕ, 2023)
This study focuses on analyzing the architectural solutions for designing the user interface of a mobile application. The aim of this research is to evaluate various research methods and guidelines for IOS and Android platforms that can enhance the efficiency of using mobile applications. The outcome of this research includes an extensive examination of user interface research methods and existing guidelines for IOS and Android platforms.